Genetic Variation of New Purple-Fleshed Sweet Potato (Ipomoea batatas L.) Genotypes in Indonesia by Multivariate Analysis - Debby Ustari; Arif Affan Wicaksono; Vergel Concibido; Tarkus Suganda; Dedi Ruswandi; null Ruminta; Agung Karuniawan (International Journal of Agronomy)
Purple-fleshed sweet potato (PFSP) is a major staple food and feed material in tropical countries. The pandemic of COVID-19 that encouraged healthy lifestyles worldwide further increases the importance of PFSP. Despite its importance, the investment in research to improve PFSP in Indonesia was left behind. The objective of the research was to estimate the genetic variation and genetic distance of new PFSP genotypes prior to variety release. The research trials were arranged in a randomized block design, with nine new PFSP genotypes from polycrosses breeding as treatments and three check varieties in four growing environments in West Java, i.e., Cilembu, Jatinangor, Maja, and Karangpawitan during one season. Agronomic traits data were analyzed by the multivariate analysis. The principal component analysis (PCA) showed high genetic variation of PFSP in four environments. The eigenvalue ranges from 1.92 to 5.29 in Cilembu which contributed to 80.958% variability, 0.543–6.177 which contributed variability to 92.135% in Jatinangor, 0.824–5.695 in Karangpawitan which contributed to 92.117%, and 0.822–4.797 in Maja which contributed to 86.133%. Storage root length, storage root diameter, number of roots per plant, total root weight per plant, number of marketable/commercial roots, marketable/commercial root weight, number of roots per plot, and total storage root weight have a discriminant value of more than 0.7 in PC 1. Agglomerative hierarchical clustering (AHC) showed a wide distribution obtaining two clusters in Cilembu with euclidean distance 1.92–5.29, Jatinangor 1.72–6.09, Karangpawitan 1.28–6.38, and Maja 2.05–5.09. High genetic variation in the four environments greatly supports to the development of PFSP new varieties.